Quelle définition des « petits métiers » de la pêche ? - Nastassia Reyes; Serge Bahuchet; Jean-Dominique Wahiche (Revue d'ethnoécologie)
The purpose of this article is to analyse through a double approach in legal anthropology and ethnoecology the meaning of « small trade » fishing. This segment presents more than 80% of the fishing fleet in the French Mediterranean sea. However, despite its importance,, the definition of the professional categories practising this marine activity is still imprecise. Several terms, which are not synonymous, designate non industrial fishing : artisanal, small scale, coastal, small scale coastal fishing. We will first present the terminology used in European and French legal texts. Then, to understand the limits of each of these expressions, we will focus on the fishing activities in lagoons of the Languedoc Region. Indeed, the techniques are the mean through which a fisherman accesses marine resources (fish, mollusks, shellfish). We will try to go beyond the sole technical dimension to take into the use of each of these techniques. Thus, we will show the scope of the diversity of existing practices, as well as the knowledge, perception and ways of working.It appears that the diversity of the techniques used in different marine ecosystems is the main element that differentiates small trade fishermen from other fishermen. A single denomination for artisanal fishing gives the illusion of a homogenous category where extremely various fishing practices do exist. It is this diversity that constitutes, for the fishermen, the core characteristic of their activity.Considering the gap between the legal definitions and the realities of the field, we conclude this article by proposing six parameters which allow to characterize fishing in the « small trade » business such as considered by the fishermen.